Eight Practices for Strategic Agility - Algoso, Dave (Stanford Social Innovation Review, 2019)
Rather than a glossy brochure that no one reads, your strategy should be an ongoing practice that informs your decisions and adapts as circu mstances change. A Viewpoint from the Summer 2019 issue.